Honey Supply Chain: a study in Pau dos Ferros/RN - Fernandes Júnior, José Vivaldo Machado; Silva, Napiê Galvê Araújo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The agribusiness honey has grown considerably in recent years from the high demand of society for natural products. Thus, the present work aims to analyze the supply chain of honey in the Associação Comunitária dos Agricultores Familiares do Perímetro Irrigado e Adjacências (ACAFPA) - Pau dos Ferros / RN.The type of research used to achieve the study is framed as exploratory, descriptive, documentary and case study. Concerning the nature of the data, the methods are qualitative and quantitative. The universe of study sets up a total of 16 members who actively participate in the activities of ACAFPA, and the value of the sample is 13 people. Defined as the collection instruments structured form, a standardized interview and direct observation and treatment of these data were made using descriptive statistics and content analysis. As a result, it was pointed out the improvement of beekeeping production system, due to the intervention of ACAFPA to promote the development of beekeeping, but realize that there are still limitations in the production chain. Finally, viewing, among other factors, the need to improve the applicant partners through courses and that measures are taken to enable the standardization of production processes and quality control of honey.